Development of a convenience and safety chilled sous vide fish dish: Diversification of aquacultural products. (April 2016) - Espinosa, MC; López, G; Díaz, P; Linares, MB; Garrido, MD
The dynamic expansion of the ready-to-eat seabream sector in its adaptation to new lifestyles has led to the search for new presentation formats in seabream ( Sparus aurata ). Green sauce (olive oil, wine vinegar, garlic, fresh parsley, black pepper, basil and salt) and 60 ℃ of cooking temperature were chosen by the panellists for the sous vide cooking process. Seabream fillet and sauce were packaged in polypropylene trays, cooked, chilled and stored at 2 ℃. Microbiological (total viable counts, Enterobacteriaceae, lactic acid bacteria, anaerobic psychrotrophic, moulds and yeasts, Salmonella and Listeria monocytogenes ), chemical (pH and TBARs) and sensory parameters were determined at 0, 7, 17, 34, 48 and 62 days. In the conditions used, the microbiological counts remained stable, and Salmonella and Listeria monocytogenes were absent. The acidic sauce had a positive effect on the pH of the product, and low TBARs were obtained throughout storage. The processing conditions used in the present study allowed a chilled ready-to-eat seabream product of consistently high quality up to 62 days of storage to be obtained, representing an expansion of the products offered by the aquacultural industry.